Physical Properties of La1−xEuxPO4, 0 ≤ x ≤ 1, Monazite‐Type Ceramics. Issue 12 (31st August 2015) - Thust, Anja; Arinicheva, Yulia; Haussühl, Eiken; Ruiz‐Fuertes, Javier; Bayarjargal, Lkhamsuren; Vogel, Sven C.; Neumeier, Stefan; Winkler, Björn
Abstract : Synthetic La1− x Eu x PO4 monazite‐type ceramics with 0 ≤  x  ≤ 1 have been characterized by ultrasound techniques, dilatometry, and micro‐calorimetry. The coefficients of thermal expansion and the elastic properties are, to a good approximation, linearly dependent on the europium concentration. Elastic stiffness coefficients range from 182(1) to 202(1) GPa for c 11 and from 53.8(7) to 61.1(4) GPa for c 44 . They are strongly dependent on the density of the sample. The coefficient of thermal expansion at 673 K is 8.4(3)  × 10 −6  K −1 for LaPO4 and 9.9(3)  × 10 −6  K −1 for EuPO4, respectively. The heat capacities at ambient temperature are between 101.6(8) J·(mol·K) −1 for LaPO4 and 110.1(8) J·(mol·K) −1 for EuPO4 . The difference between the heat capacity of LaPO4 and the Eu‐containing solid solutions is dominated by electronic transitions of the 4 f ‐electrons at temperatures above 75 K.